LITERATURE REVIEW: SUPPORT SYSTEM KELUARGA PADA PASIEN STROKE - Laenaya Fatika, Linda; Listyarini, Anita Dyah; Septiani, Evi; Aprilia, Fadilla Putri; Widiyawanti, Fera; Fatikasari, Fifi (Asosiasi Dosen Muda Indonesia, 2024)
ABSTRACT Stroke is a disease that attacks the arteries leading to the brain. In the 2018 Riskesdas of the Indonesian Ministry of Health, the incidence of stroke in Indonesia was 713,783 people (10.9%). The intervention that comes closest to stroke patients is the family. Family support plays an important role as a source of coping for patients in dealing with illness and undergoing the treatment process. Effective coping will have an effect on patients in dealing with and managing the problems they face. Purpose: The aim of this study was to determine the family support system for quality of life in stroke patients based on a literature search. Methods: The method in this study used secondary data analysis methods in the form of literature reviews. Literature search was carried out through Google Schoolar and PubMed. Results: The results of a literature search show that the family support system is the most important resource for patients, especially stroke patients. Conclusion: The family has an important role in improving the quality of life of stroke patients. Keywords : support, family, stroke